A interpretação da sentença com verbos simples (plain verbs): a ambiguidade em construções com os verbos abraçar e conversar em LIBRAS. - Pinto , Charridy Max Fontes (2017)
This dissertation has as object of study the ambiguity founded in sentences with simple biargumentals verbs to talk and to embrace (plain verbs) in simple and declarative sentences in Brazilian Sign Language (LIBRAS). The objective is to ascertain the phenomenon of ambiguity and its reflexes in the syntactic order of the respective verbs from the existing researches in sign language syntax. Because it is a language that has not yet been described, we intend with this work to contribute to a greater understanding regarding the functioning of the order of the constituents in a spatial syntax. The basic order founded in these languages is the SVO, but other possibilities of reordering are feasible even if, in this case, ambiguities are perceived when the arguments are reorded. According to Fisher (2014) and Quadros (1999), ambiguity would be undone from the topicalization process, however, our data showed us that topicalization maintains the ambiguity. To unmake the ambiguity and the reordering of the sentence, the semantic trait of the verb plays an important role since it is observed that when moving the arguments of the verbs like talk / embrace to the beginning of the sentence we have resulted in the nonambiguous SV order. The theory adopted was the Generative Theory, specifically the Theory of Principles and Parameters (P & P). Regarding the methodology, the Judgment of Acceptability was adopted in which the informants from their innate knowledge of language signaled the acceptability or not of the sentences. We conclude that semantic trait and verbal symmetry influence order and syntactic interpretation